2015
DOI: 10.1016/s2213-8587(15)00227-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a behavioural intervention in obese pregnant women (the UPBEAT study): a multicentre, randomised controlled trial

Abstract: National Institute for Health Research, Guys and St Thomas' Charity, Chief Scientist Office Scotland, Tommy's Charity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
758
4
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 571 publications
(797 citation statements)
references
References 25 publications
23
758
4
12
Order By: Relevance
“…Recent intervention trials have successfully increased physical activity levels among obese pregnant women (Dodd et al, 2014;Poston et al, 2015). However, similar to the women in this study, others have identified a lack of advice and support with physical activity in pregnancy, and a particular concern around safety (Weir et al, 2010;Sui and Dodd, 2013;Padmanabhan et al, 2015), while receiving physical activity advice from health professionals is a key enabler to supporting physical activity (Sui and Dodd, 2013).…”
Section: Resultsmentioning
confidence: 51%
“…Recent intervention trials have successfully increased physical activity levels among obese pregnant women (Dodd et al, 2014;Poston et al, 2015). However, similar to the women in this study, others have identified a lack of advice and support with physical activity in pregnancy, and a particular concern around safety (Weir et al, 2010;Sui and Dodd, 2013;Padmanabhan et al, 2015), while receiving physical activity advice from health professionals is a key enabler to supporting physical activity (Sui and Dodd, 2013).…”
Section: Resultsmentioning
confidence: 51%
“…All aspects of the trial, including the analyses in the present study, were approved by the National Health Service Research Ethics Committee (UK Integrated Research Application System; reference 09/H0802/5) and all participants, including women aged 16 and 17 using Fraser guidelines, provided informed written consent [11].…”
Section: Methodsmentioning
confidence: 99%
“…Second, interventions in most of the studies were implemented late, in the second or third trimester, which might not have allowed sufficient time for the intervention to be effective. The latter was true even for the relatively large-scale intervention studies published recently [28][29][30].…”
mentioning
confidence: 93%